Issues of privacy policy conflict in mobile social network - Pingshui Wang; Qinjuan Ma (International Journal of Distributed Sensor Networks)
Privacy protection in mobile social networks is a hot issue in current research. Various privacy protection policies have been proposed. However, the conflict of privacy protection policies inevitably occurs. In this article, aiming at the personalized privacy protection model proposed in our published paper, we analyzed the possible conflict between privacy policies and comprehensively considered the policy conflict brought by the resource-level relationship; meanwhile, we proposed a scheme of consistency verification for privacy policy to improve the previous personalized privacy protection model. We also verified the practical effects of the improved model by experiments on synthetic data sets.